Obtención de proteína unicelular de Kluyveromyces marxianus con el aprovechamiento de residuos agroindustriales (suero de mantequilla) y sus aplicaciones - González Rodas, Gina Stephanie (2022)
The constant concern for managing agro-industrial residues requires the search for new applications that efficiently take advantage of these residues and reduce the environmental impact. A viable alternative is the production of single-cell protein (SCP) that, through technological development, converts waste such as buttermilk into products with high added value. For this reason, the present research project aimed to obtain a single-cell protein of Kluyveromyces marxianus from fermentation with buttermilk and, through a bibliographic review, determine its possible applications in human and animal nutrition. For this, the yeast was grown in a batch system in a culture medium composed of deproteinized buttermilk and supplemented with peptone and glucose at 2% and 3% as the only energy sources, at a pH of 4.5, a temperature of 30 °C at 100 rpm for 24h. An analysis of variance ANOVA and the Tukey test (p<0.05) were applied to determine statistical significance based on cell yield. It was found that the maximum protein yield was 27.07% with whey supplemented with 3% glucose. The characterization of the produced biomass resulted in a high protein content of 27.73%, fat 16.98%, and ash 23.55%, which make it a product of high nutritional value compared to other traditional protein sources. Finally, in determining its possible applications, a systematic review was carried out using the PRISMA statement, where 11 studies were selected for analysis. The results showed that the biomass of this yeast could replace conventional balanced protein sources and be applied directly as a protein ingredient for aquaculture diets (salmon, trout, and tilapia), poultry, and cattle. However, its incorporation into the diet is still developing, so applying new techniques and tools remains challenging.